Promoting calls to a quitline: quantifying the influence of message theme, strong negative emotions and graphic images in television advertisements. Issue 4 (2nd February 2011) - Farrelly, Matthew C; Davis, Kevin C; Nonnemaker, James M; Kamyab, Kian; Jackson, Christine
Abstract : Objective: To understand the relative effectiveness of television advertisements that differ in their thematic focus and portrayals of negative emotions and/or graphic images in promoting calls to a smokers' quitline. Methods: Regression analysis is used to explain variation in quarterly media market-level per smoker calls to the New York State Smokers' Quitline from 2001 to 2009. The primary independent variable is quarterly market-level delivery of television advertisements measured by target audience rating points (TARPs). Advertisements were characterised by their overall objective—promoting cessation, highlighting the dangers of secondhand smoke (SHS) or other—and by their portrayals of strong negative emotions and graphic images. Results: Per smoker call volume is positively correlated with total TARPs (p<0.001), and cessation advertisements are more effective than SHS advertisements in promoting quitline call volume. Advertisements with graphic images only or neither strong negative emotions nor graphic images are associated with higher call volume with similar effect sizes. Call volume was not significantly associated with the number of TARPs for advertisements with strong negative emotions only (p=0.71) or with both graphic images and strong emotions (p=0.09). Conclusions: Exposure to television advertisements is strongly associated with quitline call volume, and both cessation and SHS advertisements can be effective. The use of strong negative emotions in advertisements may be effective in promoting smoking cessation in the population but does not appear to influence quitline call volume. Further research is needed to understand the role of negative emotions in promoting calls to quitlines and cessation more broadly among the majority of smokers who do not call quitlines.